History and memory in African-American culture - Fabre, Geneviève.; O'Meally, Robert G., 1948- (New York : Oxford University Press, 1994)
The relation between history and memory has become an object of increasing attention among historians and literary critics. Through a team of leading scholars, this volume offers a complex picture of the dynamic ways in which an African-American historical identity constantly invents and transmits itself in books, art, performance, and oral documents.
The Black writer's use of memory / Melvin Dixon -- The politics of fiction, anthropology, and the folk : Zora Neale Hurston / Hazel Carby -- W.E.B. Du Bois and the struggle for American historical memory / David W. Blight -- African-American commemorative : celebrations in the nineteenth century / Geneviève Fabre -- National identity and ethnic diversity : "of Plymouth Rock and Jamestown and Ellis Island" : or, ethnic literature and some redefinitions of America / Werner Sollors -- International beacons of African-American memory : Alexandre Dumas père, Henry O. Tanner, and Josephine Baker as examples of recognition / Michel Fabre -- On the wrong side of the fence : racial segregation in American cemeteries / Angelika Krüger-Kahloula -- What one cannot remember mistakenly / Karen Fields -- History-telling and time : an example from Kentucky / Alessandro Portelli -- Memory and mass culture / Susan Willis -- Performing the memory of difference in Afro-Caribbean dance : Katherine Dunham's choreography, 1938-87 / VéVé Clark -- "With a whip in his hand" : rape, memory, and African-American women / Catherine Clinton -- Sherley Anne Williams' Dessa Rose : history and the disruptive power of memory / Andrée-Anne Kekeh -- Art history and Black memory : toward a "blues aesthetic" / Richard J. Powell -- On Burke and the vernacular : Ralph Ellison's boomerang of history / Robert G. O'Meally -- The journals of Charlotte L. Forten-Grimké : Les Lieux de Mémoire in African-American women's autobiography / Nellie Y. McKay -- Washington Park / Robert Stepto -- Between memory and history : Les Lieux de Mémoire / Pierre Nora.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: African Americans -- History; African Americans -- Historiography; African American arts; American literature -- African American authors; Noirs américains -- Histoire; Noirs américains -- Historiographie; Arts noirs américains.; SOCIAL SCIENCE -- Ethnic Studies -- African American Studies; African American arts; African Americans; African Americans -- Historiography; American literature -- African American authors; Geschichte; Geschichtsschreibung; Kultur; Literatur; Schwarze; USA; Aufsatzsammlung; Schwärze; Historisch besef; Geschiedschrijving; Zwarten; Noirs américains -- Histoire; Écrivains noirs américains -- États-Unis.; Arts noirs américains -- États-Unis.; Noirs américains -- Historiographie; Art noir américain.; Littérature américaine -- Auteurs noirs américains.; Geschichte 1800-1990.; Black persons -- Culture -- History; United States; History